Gender Differences in the Role of Perceived Romantic Relationship Importance on Life Satisfaction: A Study of Single Adults in Indonesia’s Cultural Context - Olivia Rachel Lolo; Karel Karsten Himawan (Universitas PGRI Yogyakarta, 2026)
Life satisfaction is a key component of subjective well-being, influenced by psychological, social, and cultural factors, including perceptions of romantic relationships. In Indonesia’s collectivist and religious culture, marital status is often associated with moral maturity and social accomplishment, which may shape how individuals, particularly singles, perceive the importance of romantic relationships. This study examines whether the perceived importance of romantic relationships predicts life satisfaction among single adults. A total of 370 single participants (mean age = 28.79; SD = 4.074) were recruited through purposive sampling. Instruments included the Brief Measure of Relationship Importance (BMRI) and the Satisfaction with Life Scale (SWLS). Linear regression analysis revealed that perceived romantic relationship importance significantly predicted life satisfaction among male participants (4,3%), but not among females. These findings indicate gender differences in how romantic values relate to psychological well-being and highlight the potential influence of cultural expectations surrounding relationships and life satisfaction in the Indonesian context. Keywords: life satisfaction, relationship importance, romantic relationship, single, unmarried